2005
DOI: 10.17221/5654-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental disorders in pet dogs

Abstract: Oral disorders of the dog represent for veterinarians a medical challenge and an important field of interest from the economical point of view. Although many epidemiological studies on dental diseases in beagles bred under controlled conditions have been realized, information on frequency of these alterations in populations of pet dogs, especially in Central Europe, is far from complete. The aim of our study was to assess the prevalence of the most common oral diseases in dogs in a Czech urban region. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
3
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 34 publications
14
114
3
20
Order By: Relevance
“…The study revealed that the most common oral diseases in the dogs were periodontal disease, dental calculus and loosening of the teeth. The same results have been reported by other authors (Page and Schroeder, 1982;Harvey et al, 1994;Hoffmann and Gaengler, 1996;Genco et al, 1998;Gorrel, 1998;Lund et al, 1999;Kyllar et al, 2005). In this study two cases of oral tumours, single case of dental caries, two case of enamel hypoplasia and one case of gingival hyperplasia were also observed.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The study revealed that the most common oral diseases in the dogs were periodontal disease, dental calculus and loosening of the teeth. The same results have been reported by other authors (Page and Schroeder, 1982;Harvey et al, 1994;Hoffmann and Gaengler, 1996;Genco et al, 1998;Gorrel, 1998;Lund et al, 1999;Kyllar et al, 2005). In this study two cases of oral tumours, single case of dental caries, two case of enamel hypoplasia and one case of gingival hyperplasia were also observed.…”
Section: Resultssupporting
confidence: 92%
“…It was more prevalent in dog feed with homemade food than dog feed with commercial diets. These findings were in consistent with several previous studies (Krasse and Brill, 1960;Page and Schroeder, 1982;Genco et al 1998;Lund et al, 1999;Gorrel, 1998;Kyllar et al, 2005;Allmuça et al, 2015), and contrary to some other studies (Rosenberg et al, 1966, Saxe , 1967) who noted that disease developed spontaneously despite the diet type. Various authors (Rosenberg et al, 1966) observed that 95% of domestic dogs, feed with homemade food or commercial diets showed large deposits since the age of 26 months.…”
Section: Age Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…The owners stated that they had observed no disease symptoms in the animal. Analysis performed by veterinarians showed that dental disorders in dogs and cats are relatively frequent in the Czech Republic (Kyllar and Witter 2005), which is in contrast with the observations of the owners (no disease symptoms noticed).…”
Section: Discussioncontrasting
confidence: 59%
“…Beslenme sonrası ağız bakımını sağlayacak uygulamaların yapılmaması periodontal bozukluk riskini artırır. Bazı bakteriler direk veya indirek olarak periodontal hastalıkların etiyolojisinde rol oynar [1,12,13] . Çalışmadaki hasta köpeklerin orta yaşlı ve yaşlı katagorisinden ve küçük-orta boyutlu ırktan olması, beslenmeler sonrası ağız bakımı uygulanmaması yukarıda belirtilen klasik literatür bulgularıyla uyumludur.…”
Section: Tartişma Ve Sonuçunclassified